2021
DOI: 10.1007/s10875-020-00922-3
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Influenza Vaccine: Uptake, Attitude, and Knowledge Among Patients Receiving Immunoglobulin Replacement Therapy

Abstract: Influenza is a potential cause of severe disease in the immunocompromised. Patients with hypogammaglobulinemia, in spite of adequate replacement therapy, are at risk of significant morbidity and adverse outcomes. A seasonal vaccine is the primary prophylactic countermeasure to limit disease. The aim of this study was to evaluate the attitude, knowledge, and influenza vaccine uptake among Irish patients receiving immunoglobulin replacement therapy (IgRT), as well as uptake in co-habitants. Fifty-seven percent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Regarding self-reported vaccination uptake, pneumococcal had the highest rate (16.1%), followed by meningococcal (7.2%), and HZ (4.9%). These findings are of extreme concern and are significantly lower than the values of 77% for seasonal influenza among Irish patients receiving immunoglobulin replacement therapy [ 25 ] and of 41% for pneumococcal vaccination among patients with chronic conditions in France [ 26 ]. Similar values of uptake have been observed for pneumococcal and influenza vaccinations with only 13.9% and 1.5% among patients with inflammatory arthritis in Bulgaria [ 27 ], 7.8% of diabetic patients in China [ 28 ], and 7% of chronic obstructive pulmonary disease patients who have received the influenza vaccine in Saudi Arabia [ 29 ]; in China, 3.29% and 6.69% of chronic disease patients aged < 65 years and ≥65 years have received the pneumococcal vaccine [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding self-reported vaccination uptake, pneumococcal had the highest rate (16.1%), followed by meningococcal (7.2%), and HZ (4.9%). These findings are of extreme concern and are significantly lower than the values of 77% for seasonal influenza among Irish patients receiving immunoglobulin replacement therapy [ 25 ] and of 41% for pneumococcal vaccination among patients with chronic conditions in France [ 26 ]. Similar values of uptake have been observed for pneumococcal and influenza vaccinations with only 13.9% and 1.5% among patients with inflammatory arthritis in Bulgaria [ 27 ], 7.8% of diabetic patients in China [ 28 ], and 7% of chronic obstructive pulmonary disease patients who have received the influenza vaccine in Saudi Arabia [ 29 ]; in China, 3.29% and 6.69% of chronic disease patients aged < 65 years and ≥65 years have received the pneumococcal vaccine [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ballow et al reported 76% and 74% influenza vaccine uptake for pediatric and adult patients with B cell defects (X-linked agammaglobulinemia, CVID, hypogammaglobulinemia) for the 2016–2017 influenza season in a survey of US IEI patients [ 45 ]. Cox et al reported similar uptake of 76% for the 2019–2020 season in adult IEI patients receiving regular immunoglobulin replacement at a single Irish center [ 46 ]. Methodology for both studies was patient self-report rather than caregiver report validated by review of vaccine records as in our study.…”
Section: Discussionmentioning
confidence: 99%